Chapter The protection of Posidonia oceanica (L.) Delile and the management of its beach-cast leaves. The italian juridical framework - Lolli, Ilaria (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
Posidonia oceanica plays a key role both in the marine environment and for coastal ecosystems and therefore enjoys special protection at international, European and national level. However, the rules protecting Posidonia in sea apply to clearly defined areas, outside of which protection needs must be weighed against other interests at stake. As for management of beach-cast leaves, the interventions of the legislator have left over years a fragmentary and lacking framework. Art. 5 of Law 60/2022, the latest addition to the framework, appears still far from providing a comprehensive regulation.